Decreased Water Use in a Super-Intensive Olive Orchard Mediates Arthropod Populations and Pest Damage - González-Zamora, José Enrique; Alonso-López, Maria Teresa; Gómez-Regife, Yolanda; Ruiz-Muñoz, Sara (Agronomy (Basel), 2021)
In Spain, water use in agriculture is expected to become limited by resources in the future. It is pertinent to study the effect of decreased irrigation on the presence of pests, plant damage, and arthropod communities in a super-intensive olive orchard examined from 2017 to 2019. Arthropods were studied with visual and vacuum sampling methods in two irrigation treatments (T1—control and T2—Regulated Deficit Irrigation (RDI)). Univariate analyses showed that the total arthropod abundance was significantly greater in T1 than in T2 in 2018 and 2019, mostly due to Diptera Nematocera. Visual sampling revealed that the feeding damage produced by Eriophyidae (Trombidiformes) was significantly lower in T2 in 2018 and 2019: 10–40% of shoots were affected in the late season compared with 50–60% affected for T1. The feeding symptoms caused by Palpita unionalis Hübner (Lepidoptera: Crambidae) and Zelleria oleastrella (Milliere) (Lepidoptera: Yponomeutidae) were significantly less for T2 than for T1. Multivariate principal response curves showed significant differences between irrigation strategies in the 2018 and 2019 data for both sampling methods. In conclusion, irrigation schemes with restricted water use (T2—RDI) help to reduce the abundance of several types of pests in olive crops, especially of those that feed on the plants’ new sprouts.